Effects of magnesium sulfate and dioctyl sodium sulfosuccinate on fecal hydration, output and systemic hydration in healthy horses - Alonso, J. M. [UNESP]; Esper, C. S. [UNESP]; Rosa, G. S. [UNESP]; Schmitt, F. P. [UNESP]; Araujo, F. L. [UNESP]; Melo Neto, G. B. [UNESP]; Pantoja, J. C. F. [UNESP]; Watanabe, M. J. [UNESP]; Alves, A. L. G. [UNESP]; Rodrigues, C. A. [UNESP]; Hussni, C. A. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
Magnesium sulphate (MS) and dioctyl sodium sulphosuccinate (DSS) are laxative drugs frequently used for the treatment of impactions. The aim of this study was to compare the effects of MS and DSS in fecal hydration, output and systemic hydration in healthy horses. Five healthy horses received 3 treatments with a 21-day interval. Treatment 1 was performed with administration of 4 liters of warm water; treatment 2: administration of 4 liters of warm water associated with 1g/kg of MS; and treatment 3: administration of 4 liters of warm water associated with 20mg/kg DSS. General and specific physical examination of the digestive system were performed, alongside with packed cell volume and total plasma protein measurement, abdominal ultrasonography and quantification of the amount and hydration of feces, before and 6, 12, 24, 36 and 48 hours after the treatments. No adverse effects were observed. The administration of laxatives promoted greater fecal output and hydration without resulting in systemic dehydration, yet no differences were observed between treatments. The absence of adverse effects of DSS demonstrates the safety of its use as a laxative drug at a dose of 20mg/kg. Studies comparing the effects of the laxative drugs in horses with large colon impaction are needed.
Keywords: laxatives; dehydration; colon impaction